2006
DOI: 10.1007/s10310-006-0221-z
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variation in wood stiffness and strength properties of hybrid larch (Larix gmelinii var. japonica × L. kaempferi)

Abstract: Genetic parameters for wood stiffness and strength properties were estimated in a 29-year-old hybrid larch stand (Larix gmelinii var. japonica × Larix kaempferi). The study included 19 full-sib larch families from Hokkaido, northern Japan. Implications of these genetic parameters in wood quality improvement are subsequently discussed. Traits included in the analyses were the dynamic modulus of elasticity of green logs (E log ), the modulus of elasticity (MOE), the modulus of rupture (MOR), compression strength… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
38
2
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(52 citation statements)
references
References 11 publications
(13 reference statements)
10
38
2
1
Order By: Relevance
“…These results confirmed the low heritability of wood properties in juvenile KUMAR (2004) and KUMAR et al (2002) mention that the study of this variable should be continued and it should be very careful because most genetic programs are based on the selection of individuals for fast production and this has a negative impact on the mechanical properties of the tree (FUJIMOTO et al, 2006). Among wood properties, only ED lumber and ED dried exhibited a significantly positive genetic correlation.…”
Section: Genotypic Correlationsupporting
confidence: 58%
See 2 more Smart Citations
“…These results confirmed the low heritability of wood properties in juvenile KUMAR (2004) and KUMAR et al (2002) mention that the study of this variable should be continued and it should be very careful because most genetic programs are based on the selection of individuals for fast production and this has a negative impact on the mechanical properties of the tree (FUJIMOTO et al, 2006). Among wood properties, only ED lumber and ED dried exhibited a significantly positive genetic correlation.…”
Section: Genotypic Correlationsupporting
confidence: 58%
“…While in the present study with teak, comparison of the relationships of young and adult wood have not been done, other studies have made this comparison (FUJIMOTO et al, 2006) and they have concluded that it is possible to make an effective selection of clones at early ages without altering the quality of adult trees.…”
Section: Genotypic Correlationmentioning
confidence: 84%
See 1 more Smart Citation
“…In hybrid larch (L. gmelinii var. japonica 9 L. kaempferi), Fujimoto et al [16] reported a strong genetic correlation between average The abbreviations for traits are the same as in Table 1 wood density at breast height and green log MOE measured by a vibration method (r g = 0.79), and between average wood density and lumber MOE obtained by a bending test (r g = 0.87). The genetic relationship between wood density and SWV in our research was similar to what was found in these previous reports related to L. kaempferi.…”
Section: Discussionmentioning
confidence: 97%
“…Fukatsu et al [15] reported a positive genetic correlation between wood density and basal area. In hybrid larch, a strong negative genetic correlation between wood density and radial growth rate, and a weak negative genetic correlation between MOE and DBH were reported in Larix gmelinii 9 L. kaempferi hybrids [16,17], and a strong negative genetic correlation between DBH and MOE was reported in Larix decidua 9 L. kaempferi hybrids [18]. To predict how the selection of a trait will affect correlated traits in the following generations of L. kaempferi, more research is necessary.…”
Section: Introductionmentioning
confidence: 91%